2019
DOI: 10.1016/j.neuron.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Subcortical and Deep Cortical Activity in the Primate Brain Using Transcranial Focused Ultrasound Stimulation

Abstract: Summary The causal role of an area within a neural network can be determined by interfering with its activity and measuring the impact. Many current reversible manipulation techniques have limitations preventing their application, particularly in deep areas of the primate brain. Here, we demonstrate that a focused transcranial ultrasound stimulation (TUS) protocol impacts activity even in deep brain areas: a subcortical brain structure, the amygdala (experiment 1), and a deep cortical region, the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
256
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(281 citation statements)
references
References 36 publications
22
256
3
Order By: Relevance
“…1b) delivered ultrasound uniformly to neurons throughout our field of view. We used a frequency of 300 kHz, within the range utilized in recent studies in a variety of organisms Folloni et al, 2019;Lee et al, 2015;Lee et al, 2016a;Legon et al, 2018a;Legon et al, 2018b;Legon et al, 2014;Leo Ai, 2018;Wattiez et al, 2017), and continuous-wave stimulation, which was found to be as effective as pulsed ultrasound (King et al, 2013). The interpulse interval was fixed at 20 sec to allow a return to baseline.…”
Section: Focused Ultrasound Robustly Activates Cortical Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b) delivered ultrasound uniformly to neurons throughout our field of view. We used a frequency of 300 kHz, within the range utilized in recent studies in a variety of organisms Folloni et al, 2019;Lee et al, 2015;Lee et al, 2016a;Legon et al, 2018a;Legon et al, 2018b;Legon et al, 2014;Leo Ai, 2018;Wattiez et al, 2017), and continuous-wave stimulation, which was found to be as effective as pulsed ultrasound (King et al, 2013). The interpulse interval was fixed at 20 sec to allow a return to baseline.…”
Section: Focused Ultrasound Robustly Activates Cortical Neuronsmentioning
confidence: 99%
“…In contrast, focused ultrasound (FUS) has the potential to modulate neural activity in deep-brain regions with millimeter spatial precision based on the penetrance of sound waves in bone and soft tissue. Recently, transcranial FUS in the frequency range of 0.25-1 MHz and intensity of 1-100 W/cm 2 (ISPPA) has been shown to elicit neural and behavioral responses in small King et al, 2013;Sharabi et al, 2018;Tufail et al, 2010;Ye et al, 2016;Younan et al, 2013) and large (Dallapiazza et al, 2018;Deffieux et al, 2013;Folloni et al, 2019;Lee et al, 2016b;Verhagen et al, 2019;Wattiez et al, 2017;Yoo et al, 2011) model animals and humans (Lee et al, 2015;Lee et al, 2016a;Legon et al, 2018a;Legon et al, 2014;Leo Ai, 2018) without genetic or chemical alterations or deleterious side effects, even with chronic stimulation . These studies have driven widespread interest in the development of FUS as a research tool in neuroscience and a strategy for disease treatment (Naor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of neural stimulation might be able to provide causal evidence of cerebellar compensation in brain disorders, and indeed, recent studies in neuropsychiatry report behavioral improvement after cerebellar stimulation [129,130]. Technological advancements that allow targeting small and deep brain structures [131][132][133][134][135] underscore the potential for cerebellar stimulation to become a useful therapeutic modality in the clinical treatment of cognitive dysfunction. Recent reports also suggest that it might be relevant to investigate surgical correction of gross cerebellar structural abnormalities such as Chiari malformation and posterior fossa arachnoid cysts as an additional cerebellar-focused intervention to relieve brain-wide dysfunction [136].…”
Section: Cerebellar Cognitive Reserve (Guell X Schmahmann Jd)mentioning
confidence: 99%
“…Pilot studies have investigated the neural effects of ultrasound parameters, such as ultrasound fundamental frequencies (UFF), intensities (UI), durations (UD), duty cycles (UDC), pulse repetition frequencies (UPRF), etc. Besides a few human studies (Hameroff et al, 2013;Lee et al, 2016b;Legon et al, 2014), animal models, such as worms (Ibsen et al, 2015;Kubanek et al, 2018;Zhou et al, 2017), rodents (Tufail et al, 2010;Ye et al, 2016;Yu et al, 2016), rabbits , swine (Dallapiazza et al, 2018), and monkeys Folloni et al, 2019), have been utilized to investigate the effects of ultrasonic parameters and acoustic-induced effects. tFUS have been observed to induce behavioral changes, e.g.…”
Section: Introductionmentioning
confidence: 99%